Consumer Behavior in Multichannel Marketing: A Systematic Literature Review - Akyas, Ghina Annisa; Chan, Arianis; Tresna, Pratami Wulan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This article summarizes research on Consumer Behavior in Multichannel Marketing published in Scopus from 2018 to 2024 using the Systematic Literature Review (SLR) method. The collected data was processed following the PRISMA guidelines, then analyzed in four stages, namely identification, screening, eligibility, and inclusion. The inclusion criteria set were: (1) Focus on consumer behavior in the context of multichannel marketing. (2) The article uses empirical methods (surveys, experiments, panel data) or contextual methods that explain consumer behavior. The results of the study show: (1) That Consumer Behavior in Multichannel Marketing is influenced by channel migration, product attributes, service quality, and media management; (2) Product and category attributes are key in explaining consumer channel choices; (3) Consistency of service quality across physical and digital channels; and (4) The need for multichannel behavioral segmentation so that marketing strategies are more targeted.